2021
DOI: 10.3390/ijms221810057
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functions of the Fatty Acid and Retinol Binding Protein (FAR) Gene Family Revealed by Fungus-Mediated RNAi in the Parasitic Nematode, Aphelenchoides besseyi

Abstract: RNA interference (RNAi) is a powerful tool for the analysis of gene function in nematodes. Fatty acid and retinol binding protein (FAR) is a protein that only exists in nematodes and plays an important role in their life activities. The rice white-tip nematode (RWTN), Aphelenchoides besseyi, is a migratory endoparasitic plant nematode that causes serious damage in agricultural production. In this study, the expression levels of eight RWTN genes were effectively decreased when RWTN was fed Ab-far-n (n: 1–8) hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In previous studies, eight Ab-far genes were identified in RWTN, but their functions vary. Among these, Ab-far-1 has been shown to probably be involved in the reproduction and pathogenic processes of nematodes [ 26 , 39 , 47 ]. However, the detailed functions and mechanisms of Ab-far-1 in the parasitism and pathogenicity process of nematodes have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, eight Ab-far genes were identified in RWTN, but their functions vary. Among these, Ab-far-1 has been shown to probably be involved in the reproduction and pathogenic processes of nematodes [ 26 , 39 , 47 ]. However, the detailed functions and mechanisms of Ab-far-1 in the parasitism and pathogenicity process of nematodes have not been studied.…”
Section: Discussionmentioning
confidence: 99%